1999
DOI: 10.1590/s0036-46651999000500004
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytosis: association between ABO blood groups and reactivity to the trichophytin

Abstract: The authors investigated the relationship between dermatophytosis and ABO blood groups through blood typing, identification of isolated dermatophytes and specific cellular immune response of 40 individuals carriers of this mycosis. They verified that the fungus Trichophyton rubrum, isolated from 54.5% of the patients, was more frequent in individuals belonging to blood group A. The cellular immune response, evaluated through the trichophytin antigen, was positive in 25% of the studied patients; the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…on the skin mucous membranes and bloodstream, the infections rate was found to be higher in individual with blood group type O compared to other blood group [7,8]. In mold infection, a previous study reported a higher prevalence of dermatophytes infection, among patients with blood group A [9,10]. The study was consistent with Candida spp.…”
Section: Introductionmentioning
confidence: 69%
“…on the skin mucous membranes and bloodstream, the infections rate was found to be higher in individual with blood group type O compared to other blood group [7,8]. In mold infection, a previous study reported a higher prevalence of dermatophytes infection, among patients with blood group A [9,10]. The study was consistent with Candida spp.…”
Section: Introductionmentioning
confidence: 69%
“…According to the latest studies carried out in Brazil, the most isolated species in chronic infections of tinea ungueum and pedis has been the T. rubrum (6,9,16,23). Although this disease is not serious in terms of mortality or physical sequelae, it has significant clinical consequences, mainly regarding aesthetic and chronic aspects of the infection, besides therapeutics difficulties (17).…”
Section: Introductionmentioning
confidence: 99%
“…8 De acordo com os autores, os indivíduos que têm esses antígenos eritrocíticos seriam mais suscetíveis ao desenvolvimento de dermatofitoses generalizadas e resistentes ao tratamento do que os indivíduos não providos desses antígenos. Recentemente, Vilani-Moreno et al, 9 ao investigarem a relação entre dermatófitos e grupo sangüíneo ABO, encontraram um número maior de pacientes pertencentes ao grupo sangüíneo A e infectados pelo T. rubrum; entretanto, não obtiveram evidência estatística de que esses indivíduos eram mais suscetíveis às dermatofitoses.…”
Section: Introductionunclassified